The Rural Superintendency: Reconsidering the Administrative Farm System - Stephen L. Jacobson (Journal of Research in Rural Education, 1988)
This paper examines the role and preparation of rural superintendents by reconsidering the informal administrative farm system that presently exists. The first part of the paper reports the findings of a comparative case study that examined effective schools in rural settings. The second part of the paper reports rural-suburban salary, recruitment and retention disparities. The paper concludes with recommendations for a proposed administrative preparation program designed to improve the quality of educational leadership in small rural districts.